Isolation and characterization of new lignin streams derived from extractive-ammonia (EA) pretreatment - Sousa, Leonardo da Costa; Foston, Marcus; Bokade, Vijay V.; Azarpira, Ali; Lu, Fachuang; Ragauskas, Arthur J.; Ralph, John; Dale, Bruce E.; Balan, Venkatesh (Green Chemistry, 2016)
One of the key challenges facing lignin conversion to fuels and chemicals is related to the level of carbohydrate and ash impurities found in extracted lignin. Structural modifications of lignin may also occur as a result of biomass pretreatment and harsh lignin extraction protocols. Extractive-Ammonia (EA) is a new pretreatment technology that uses liquid ammonia to cleave lignin-carbohydrate complexes, decrystallize cellulose, solubilize lignin, and selectively extract Lignin from lignocellulosic biomass, enabling better utilization of both lignin and carbohydrate components in a biorefinery. The EA-based biorefinery produces two different lignin-rich streams, with different properties, that could potentially be upgraded to fuels and chemicals using green processes. In this work, a water/ethanol-based fractionation method was developed to enrich the ammonia-soluble extractives, resulting in a major product stream containing 92% lignin. Detailed characterization of the various streams resulting from EA treatment, including compositional analysis, structural characterization by nuclear magnetic resonance (NMR) spectrometry, elemental analysis, molecular weight analysis, and thermo-gravimetric analysis provides a broad evaluation of the EA derived lignin product stream structures and properties, assessing their potential for commercial applications. In summary, EA-derived lignins preserve much of lignin's functionality, including the sensitive (3-aryl ether units. Nitrogen incorporation was observed in the lignin-rich streams, notably due to the presence of hydroxycinnamoyl amides formed during ammonia pretreatment.

Next-generation ammonia pretreatment enhances cellulosic biofuel production - Sousa, Leonardo da Costa; Jin, Mingjie; Chundawat, Shishir P. S.; Bokade, Vijay V.; Tang, Xiaoyu; Azarpira, Ali; Lu, Fachuang; Avci, Utku; Humpula, James; Uppugundla, Nirmal; Gunawan, Christa; Pattathil, Sivakumar; et al. (Energy & Environmental Science, 2016)
A new liquid ammonia pretreatment methodology called Extractive Ammonia (EA) was developed to simultaneously convert native crystalline cellulose I-beta (CI) to a highly digestible cellulose IIII (CIII) allomorph and selectively extract up to B45% of the lignin from lignocellulosic biomass with near-quantitative retention of all polysaccharides. EA pretreated corn stover yielded a higher fermentable sugar yield compared to the older Ammonia Fiber Expansion (AFEX) process while using 60% lower enzyme loading. The EA process preserves extracted lignin functionalities, offering the potential to co-produce lignin-derived fuels and chemicals in the biorefinery. The single-stage EA fractionation process achieves high biofuel yields (18.2 kg ethanol per 100 kg untreated corn stover, dry weight basis), comparable to those achieved using ionic liquid pretreatments. The EA process achieves these ethanol yields at industrially-relevant conditions using low enzyme loading (7.5 mg protein per g glucan) and high solids loading (8% glucan, w/v).